2021
DOI: 10.31557/apjcp.2021.22.6.1761
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Histological Data Effect of Silybum marianum and Suaeda vermiculata Against Doxorubicin Induced Toxicity in Male Rats

Abstract: Objective: Silybum marianum and Suaeda vermiculata are popular plants wealthy in cancer prevention agents. There is no enough research on both plants since they are not available in many places. They are widely spread in Egypt. Methods: This research was performed to estimate their antimicrobial effect as well as their hepatoprotective effect against strong drugs inducing oxidative stress such as doxorubicin which may be a chemotherapeutic operator utilized to treat different sorts of cancer and demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Suaeda vermiculata (SV) is a halophytic plant rich in antioxidant and antimicrobial constituents. 37 SVE was reported to treat respiratory diseases such as asthma, 48 has an antimicrobial effect 49 and treats viral diseases. 31 Mohammed SAA et al, demonstrated that SVE has no deleterious effects on kidney and liver enzymes, lipid profiles, or glucose, with only a mild lowering effect on triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suaeda vermiculata (SV) is a halophytic plant rich in antioxidant and antimicrobial constituents. 37 SVE was reported to treat respiratory diseases such as asthma, 48 has an antimicrobial effect 49 and treats viral diseases. 31 Mohammed SAA et al, demonstrated that SVE has no deleterious effects on kidney and liver enzymes, lipid profiles, or glucose, with only a mild lowering effect on triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Suaeda vermiculata (SV) is a halophytic plant rich in antioxidant and antimicrobial constituents 37 . SVE was reported to treat respiratory diseases such as asthma, 48 has an antimicrobial effect 49 and treats viral diseases 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations